Penerapan Model Cooperative Learning Type TGT Berbantuan Media Quizwhizzer Terhadap Hasil Belajar Peserta Didik: Application of Cooperative Learning Type TGT Model with Quizwhizzer Media Assistance to Student Learning Outcomes - Mardiana, Rosa; Solihat, Ai Nur; Gumilar, Rendra (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The main problem related to this research is the low learning outcomes of students in economic subjects. This study aims to determine the existence of an increase in student learning outcomes before and after treatment as well as differences in the improvement of student learning outcomes in experimental classes using the cooperative learning model team games tournament (TGT) type assisted by quizwhizzer media and control classes using conventional learning models after treatment. The research was conducted at SMA Negeri 1 Sindangkasih. The research method used was quasi-experimental method. The population in this study is class XI IPS SMA Negeri 1 Sindangkasih, using purposive sampling technique with a total of 72 students. The instrument used in this study was a 30 item ganta choice question. Data analysis techniques using the help of SPSS 25, namely paired sample t-test and independent sample t-test with a significant level of 5% or 0.05. Based on the results of the study, the Sig. (2-tailed) of 0.000 so that it can be concluded that there is a difference in the improvement of student learning outcomes in the experimental class using the cooperative learning model team games tournament (TGT) assisted by quizwhizzer media after treatment with the control class using the conventional learning model after treatment.